1993
DOI: 10.1111/j.1365-4362.1993.tb00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Tinea Capitis in Saudi Arabia

Abstract: Although none of the patients owned pets, the predominance of M. canis may be explained by the large number of cats in the neighborhood. The disappearance of favus due to T. schoenleinii may be due to improved socioeconomic conditions. Our results agreed with two previous reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 4 publications
4
34
2
Order By: Relevance
“…T. verrucosum and T. mentagrophytes are occasionally encountered pathogens. M. canis , the major pathogen in the United Arab Emirates, 22 Qatar, 23 Kuwait, 24 Saudi Arabia, 25 Israel, 26 and Spain, 27 was not isolated in our series. This dermatophyte has been previously reported from this region.…”
Section: Discussionmentioning
confidence: 56%
“…T. verrucosum and T. mentagrophytes are occasionally encountered pathogens. M. canis , the major pathogen in the United Arab Emirates, 22 Qatar, 23 Kuwait, 24 Saudi Arabia, 25 Israel, 26 and Spain, 27 was not isolated in our series. This dermatophyte has been previously reported from this region.…”
Section: Discussionmentioning
confidence: 56%
“…They change continually due to influences of climate, human social and antisocial activities, cultural activities, cultural habits, migration and developments in diagnosis and therapy [5][6][7]. Many studies on superficial mycoses in different parts of the world have confirmed that host susceptibility may be enhanced by moisture, warmth, specific skin chemistry, composition of sebum and perspiration, age, heavy exposure and genetic predisposition [8][9][10][11][12]. Dermatophytoses is highly contagious and represent a significant public health problem, particularly among school children [13].…”
Section: Introductionmentioning
confidence: 99%
“…Tinea capitis is unusual in children during their first year of life 4 . In the series of Venugopal and Venugopal, 5 among 240 cases of tinea capitis only two (0.8%) occurred in babies under 1 year of age. In a previous 15 year observation at our Department over 31 cases of kerion only one child had less than 2 years of age 1 …”
Section: Discussionmentioning
confidence: 99%